Risk factors and management of intraprocedural rupture during coil embolization of unruptured intracranial aneurysms: role of balloon guiding catheter - Aoki, Ken; Murayama, Yuichi; Tanaka, Yoshihiro; Ishibashi, Toshihiro; Irie, Koreaki; Fuga, Michiyasu; Kato, Naoki; Kan, Issei; Nishimura, Kengo; Nagayama, Gota (Frontiers in Neurology, 2024)
Introduction Intraprocedural rupture (IPR) is a serious complication of endovascular coil embolization of unruptured intracranial aneurysms (UIAs). Although outcomes after IPR are poor, methods to prevent subsequent neurological deterioration have not yet been investigated. We evaluated the risk factors and management strategies for IPR, particularly the role of balloon guiding catheters (BGCs) in rapid hemostasis. Methods We retrospectively reviewed all UIA cases treated with coil embolization at three institutions between 2003 and 2021, focusing on preoperative radiological data, operative details, and outcomes. Results In total, 2,172 aneurysms were treated in 2026 patients. Of these, 19 aneurysms in 19 patients (0.8%) ruptured during the procedure. Multivariate analysis revealed that aneurysms with a bleb (OR: 3.03, 95% CI: 1.21 to 7.57, p = 0.017), small neck size (OR: 0.56, 95% CI: 0.37 to 0.85, p = 0.007), and aneurysms in the posterior communicating artery (PcomA) (OR: 4.92, 95% CI: 1.19 to 20.18, p = 0.027) and anterior communicating artery (AcomA) (OR: 12.08, 95% CI: 2.99 to 48.79, p < 0.001) compared with the internal carotid artery without PcomA were significantly associated with IPR. The incidence of IPR was similar between the non-BGC and BGC groups (0.9% vs. 0.8%, p = 0.822); however, leveraging BGC was significantly associated with lower morbidity and mortality rates after IPR (0% vs. 44%, p = 0.033). Discussion The incidence of IPR was relatively low. A bleb, small aneurysm neck, and location on PcomA and AcomA are independent risk factors for IPR. The use of BGC may prevent fatal clinical deterioration and achieve better clinical outcomes in patients with IPR.